Identification of a peptide ligand for human ALDH3A1 through peptide phage display: Prediction and characterization of protein interaction sites and inhibition of ALDH3A1 enzymatic activity - Voulgaridou, Georgia-Persephoni; Theologidis, Vasileios; Xanthis, Vasileios; Papagiannaki, Eleni; Tsochantaridis, Ilias; Fadouloglou, Vasiliki E.; Pappa, Aglaia (Frontiers in Molecular Biosciences, 2023)
Aldehyde dehydrogenase 3A1 (ALDH3A1) by oxidizing medium chain aldehydes to their corresponding carboxylic acids, is involved in the detoxification of toxic byproducts and is considered to play an important role in antioxidant cellular defense. ALDH3A1 has been implicated in various other functions such as cell proliferation, cell cycle regulation, and DNA damage response. Recently, it has been identified as a putative biomarker of prostate, gastric, and lung cancer stem cell phenotype. Although ALDH3A1 has multifaceted functions in both normal and cancer homeostasis, its modes of action are currently unknown. To this end, we utilized a random 12-mer peptide phage display library to identify efficiently ALDH3A1-interacting peptides. One prevailing peptide (P1) was systematically demonstrated to interact with the protein of interest, which was further validated in vitro by peptide ELISA. Bioinformatic analysis indicated two putative P1 binding sites on the protein surface implying biomedical potential and potent inhibitory activity of the P1 peptide on ALDH3A1 activity was demonstrated by enzymatic studies. Furthermore, in search of potential ALDH3A1 interacting players, a BLASTp search demonstrated that no protein in the database includes the full-length amino acid sequence of P1, but identified a list of proteins containing parts of the P1 sequence, which may prove potential ALDH3A1 interacting partners. Among them, Protein Kinase C Binding Protein 1 and General Transcription Factor II-I are candidates of high interest due to their cellular localization and function. To conclude, this study identifies a novel peptide with potential biomedical applications and further suggests a list of protein candidates be explored as possible ALDH3A1-interacting partners in future studies.